Analisis Yuridis Putusan Hakim Terhadap Tindak Pidana Pencurian Dengan Pemberatan Yang Dilakukan Oleh Anak (Studi Kasus Putusan Nomor : 2/Pid.Sus-Anak/2022/PN.Brb) - Abdullah, Muhammad Zen; Alamsyah, Bunyamin; Alifia, Dhania (Legalitas: Jurnal Hukum, 2023)
Various criminal acts that occur in people's lives, one of which is the crime of theft which has recently been widespread and has increased in the mass media reports and electronic media. The crime of theft is really very disturbing security, order, welfare and greatly causes material and immaterial losses to the community. Therefore, it is necessary to immediately anticipate and deal with it by responding quickly and appropriately to its resolution through the applicable legal mechanism, by punishing the perpetrator/suspect with a sufficiently aggravated criminal threat, so that the crime of theft in question can be suppressed and minimized. In the court examination process in the application of criminal sanctions against the crime of theft in a burdensome situation by a child based on case Number 2/Pid.Sus-Anak/2022/PN. Brb, the problems were; a. What is the basis for the judge's legal considerations in passing a criminal decision against the crime of theft in a burdensome situation by a child and b. How is the content/order of the judge's decision against the crime of theft in a burdensome situation by a child. To answer the problem formulation listed above, the theory of sentencing, the theory of judges' legal considerations and the theory of law enforcement are used. This research is normative juridical and empirical juridical research. The type of data included primary and secondary law materials. Technique of collecting legal sources used was library study/document study on literature, legislation, and document, and also interview. From the results of the study, reflected in the basis of the judge's legal considerations in passing a criminal decision against the crime of theft in a burdensome situation by a child firearms against the defendant, with the decision to sentence the defendant to 4 (four) months, based on the decision of the case Number 2/Pid.Sus-Anak/2022/ PN.Brb. Whereas in Article 363 paragraph (2) of the Criminal Code which is violated the maximum penalty is 9 (nine) years. So it is felt that the application of the criminal decision is still very light and not optimal. The suggestion put forward is that the maximum sanctions should be given specifically to children who have repeatedly committed similar crimes as long as they are in accordance with the applicable legal provisions.